Effect of some induce chemical and biological agents against (Tilletia tritici (Bjerk) and T.laevis (Kühn) causal agents of wheat Common bunt disease (Baghdad Science Journal, 2016)
This study was conducted to evaluate the efficiency of some chemicals and biological agents to induce systemic resistance (ISR) against to wheat common bunt disease caused by the two species of fungus Tilletia tritici (Bjerk.) Wint (T. caries (Dac.) Tul.) and T. laevis Kuhn (T. foetida (Wall.) Liro. Trails in the efforts to find an alternative, safe and environmentally friendly means to control the disease. Results of this study which carried out during two consecutive seasons for the years 2012 - 2013 and 2013 - 2014 at two different environmental locations. Seed treatment by (SA 100 and 200 mg/L, 500 ?–aminobutyric acid (BABA) and 1000 mg/L, Effective Microorganisms (EM1) 40 and 150 ml/kg seeds) have led to high significant reduction in the percentage of common bunt compared with the control (plants resulting from the seeds contaminated non- treatment), While foliar treatment showed some significant differences, especially in the experiment carried out at the fields of College of Agriculture - Baghdad University compared with experiments carried out in the fields of Faculty of Agricultural Sciences -University of Sulaimania, which did not showed significant differences in most treatments. The treatment with Effective microorganisms was found efficient in reducing the infection rate compared with SA and BABA.